Demographic and mental health assessments in the adolescent brain and cognitive development study: Updates and age-related trajectories. (December 2021) - Barch, Deanna M.; Albaugh, Matthew D.; Baskin-Sommers, Arielle; Bryant, Brittany E.; Clark, Duncan B.; Dick, Anthony Steven; Feczko, Eric; Foxe, John J.; Gee, Dylan G.; Giedd, Jay; Glantz, Meyer D.; Hudziak, James J.; et al.
Abstract: The Adolescent Brain Cognitive Development (ABCD) Study of 11, 880 youth incorporates a comprehensive range of measures assessing predictors and outcomes related to mental health across childhood and adolescence in participating youth, as well as information about family mental health history. We have previously described the logic and content of the mental health assessment battery at Baseline and 1-year follow-up. Here, we describe changes to that battery and issues and clarifications that have emerged, as well as additions to the mental health battery at the 2-, 3-, 4-, and 5-year follow-ups. We capitalize on the recent release of longitudinal data for caregiver and youth report of mental health data to evaluate trajectories of dimensions of psychopathology as a function of demographic factors. For both caregiver and self-reported mental health symptoms, males showed age-related decreases in internalizing and externalizing symptoms, while females showed an increase in internalizing symptoms with age. Multiple indicators of socioeconomic status (caregiver education, family income, financial adversity, neighborhood poverty) accounted for unique variance in both caregiver and youth-reported externalizing and internalizing symptoms. These data highlight the importance of examining developmental trajectories of mental health as a function of key factors such as sex and socioeconomic environment.